2022
DOI: 10.1039/d2ta05592a
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite-free lithium metal batteries achieved with Ce-MOF membrane coating with one-dimensional continuous oxygen-containing channels for rapid migration of Li ions

Abstract: Lithium metal batteries (LMBs) offers the highest theoretical capacity (3860 mAh g−1), but has suffered from the issue of formation of lithium dendrite during device operation owing to inhomogeneous growth...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[38][39][40] Many extraordinary features of MOFs, including structural diversity, strong mechanical strength, adjustable porosity, selective ion transport, and electrical insulation, make them one of the candidate materials for membrane and current collector coatings. [41][42][43] Recently, a few reports have achieved remarkable results in boosting interfacial stability with the aid of MOF articial SEI lms on LMAs. [44][45][46][47] Wu and co-workers designed a semi-solid interphase based on coatings of Lewis acidic MOF nanoparticles inltrated with liquid electrolyte, which effectively suppresses uneven Li deposition and dendrite growth.…”
Section: Gen Chenmentioning
confidence: 99%
“…[38][39][40] Many extraordinary features of MOFs, including structural diversity, strong mechanical strength, adjustable porosity, selective ion transport, and electrical insulation, make them one of the candidate materials for membrane and current collector coatings. [41][42][43] Recently, a few reports have achieved remarkable results in boosting interfacial stability with the aid of MOF articial SEI lms on LMAs. [44][45][46][47] Wu and co-workers designed a semi-solid interphase based on coatings of Lewis acidic MOF nanoparticles inltrated with liquid electrolyte, which effectively suppresses uneven Li deposition and dendrite growth.…”
Section: Gen Chenmentioning
confidence: 99%
“…demonstrated that MOF-199 or ZIF-8 can be a protection layer on the Li or Na anode, and Zheng et al constructed a Zr-based MOF layer serving as “ionic sieves” to realize uniform Li + transport . Although trials and attempts have been made with a few kinds of MOFs in Li-metal batteries, the MIL-125­(Ti)-MOF-modified Li-metal anode has not been reported yet. Ti-based MOFs appear to be attractive due to their strong metal–ligand bonding and rigid framework.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, uneven lithium deposition can lead to the formation of dendrites, which can short-circuit the battery cell by piercing the separator, causing serious safety issues. [5][6][7][8][9] These problems greatly hinder the adoption of LMBs in industry.…”
Section: Introductionmentioning
confidence: 99%